2017
DOI: 10.1186/s12906-016-1533-y
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin ameliorates the extreme inflammatory status in sepsis through TLR4 signaling pathways

Abstract: BackgroundSepsis is one of the serious disorders in clinical practice. Recent studies found toll-like receptors 4 (TLR4) played an important role in sepsis. In this study, we tried to find the influence of Corilagin on TLR4 signal pathways in vitro and in vivo.MethodsThe cellular and animal models of sepsis were established by LPS and then interfered with Corilagin. Real-time PCR and western blot were employed to detect the mRNA and protein expressions of TLR4, MyD88, TRIF and TRAF6. ELISA was used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Corilagin (C 27 H 22 O 18 ) is an active component of many medicinal plants, with a variety of pharmacological activities including anti-tumor, anti-oxidative, anti-atherogenic, thrombolytic, anti-hypertensive, hepatoprotective, antiviral, antibacterial and anti-inflammatory effects (Zhao et al, 2008 ; Guo et al, 2010 , 2015a ; Jin et al, 2013 ; Li et al, 2017 ). Its known chemical structure was presented in our previously published paper (Zhao et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Corilagin (C 27 H 22 O 18 ) is an active component of many medicinal plants, with a variety of pharmacological activities including anti-tumor, anti-oxidative, anti-atherogenic, thrombolytic, anti-hypertensive, hepatoprotective, antiviral, antibacterial and anti-inflammatory effects (Zhao et al, 2008 ; Guo et al, 2010 , 2015a ; Jin et al, 2013 ; Li et al, 2017 ). Its known chemical structure was presented in our previously published paper (Zhao et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that it was confirmed that Corilagin attenuates lung cell damage induced by cigarette smoke (28). Some of our previous studies on Corilagin have confirmed its effects on ameliorating sepsis (21) as well as its anti-oxidative and anti-inflammatory effects (29) and suppressive effects on HSV-1 encephalitis (30). Moreover, our studies have demonstrated that IL-13 is associated with the multi-target effects of Corilagin on relieving schistosome egg-induced liver fibrosis (12, 32, 33).…”
Section: Introductionmentioning
confidence: 76%
“…Corilagin (beta-1-O-galloyl-3, 6-(R)-hexahydroxydiphenoyl-D-glucose) is a tannin with the molecular formula C 27 H 22 O 18 and is isolated from a variety of plants (20, 21). Corilagin has been shown to have an extensive pharmacological efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…chemical analysis by UPLc in the present study showed that corilagin and ellagic acid were the main components of ESEE, but other observed peaks were not identified. Many studies have reported the anti-inflammatory, anti-cancer and hepatoprotective effects of corilagin (35)(36)(37). Previous studies have also reported that ellagic acid improved hepatic steatosis and suppressed serum resistin levels in obese mice (38,39), and that ellagic acid suppresses lipid accumulation by inhibiting adipogenesis and cell proliferation (40).…”
Section: Discussionmentioning
confidence: 99%